Camrelizumab plus carboplatin and pemetrexed versus chemotherapy alone in chemotherapy-naive patients with advanced non-squamous non-small-cell lung cancer (CameL): a randomised, open-label, multicentre, phase 3 trial. Issue 3 (March 2021) - Zhou, Caicun; Chen, Gongyan; Huang, Yunchao; Zhou, Jianying; Lin, LiZhu; Feng, Jifeng; Wang, Zhehai; Shu, Yongqian; Shi, Jianhua; Hu, Yi; Wang, QiMing; Cheng, Ying; et al.
Summary: Background: Immunotherapy combined with chemotherapy has been shown to be efficacious as treatment for advanced non-squamous non-small-cell lung cancer (NSCLC) without targetable genetic aberrations; however, there is scarce evidence of the effectiveness of the combinations in the Asian population. We evaluated camrelizumab plus chemotherapy against non-squamous NSCLC in China. Methods: We did a randomised, open-label, multicentre, phase 3 trial (CameL) in 52 hospitals in China for patients with non-squamous NSCLC without EGFR and ALK alteration. Eligible patients were aged 18–70 years and had no previous systemic chemotherapy, Eastern Cooperative Oncology Group performance status of 0 or 1, and at least one measurable lesion per Response Evaluation Criteria in Solid Tumors (version 1.1). Patients were randomly assigned (1:1) to receive 4–6 cycles of carboplatin (area under curve 5 mg/mL per min) plus pemetrexed (500 mg/m 2 ) with or without camrelizumab (200 mg) every 3 weeks, followed by maintenance therapy with camrelizumab plus pemetrexed or pemetrexed alone. Medication was administered intravenously on day 1 of each 3-week treatment cycle. Randomisation was done using a centralised interactive web-response system with the block size randomly generated as four or six and stratified by sex and smoking history. The two primary endpoints were progression-free survival per blinded independent central review, in all patients and in patients who were PD-L1 positive. Primary analysis was done in the full analysis set that included all randomly assigned patients who received at least one dose of the study treatment. Herein, due to the primary endpoint being met at the interim analysis, we reported the findings of prespecified interim analysis, which only included confirmatory statistical testing for progression-free survival in all patients. Safety was assessed in the as-treated population. This study is registered with ClinicalTrials.gov, NCT03134872 (follow-up is ongoing). Findings: Between May 12, 2017, and June 6, 2018, of the 419 patients who were randomly assigned, seven did not receive assigned treatment and 412 received either camrelizumab plus chemotherapy (n=205) or chemotherapy alone (n=207). At interim analysis, median follow-up duration was 11·9 months (IQR 9·0–14·9). Progression-free survival in this interim analysis was significantly prolonged with camrelizumab plus chemotherapy than with chemotherapy alone (median 11·3 months [95% CI 9·6–15·4] vs 8·3 months [6·0–9·7]; hazard ratio 0·60 [0·45–0·79]; one-sided p=0·0001). Most common grade 3 or worse treatment-related adverse events were decreased neutrophil count (78 [38%] patients in the camrelizumab plus chemotherapy group vs 63 [30%] patients in the chemotherapy alone group), decreased white blood cell count (40 [20%] vs 30 [14%]), anaemia (38 [19%] vs 23 [11%]), and decreased platelet count (34 [17%] vs 24 [12%]). Serious treatment-related adverse events occurred in 74 (36%) patients in the camrelizumab plus chemotherapy group and 27 (13%) patients in the chemotherapy alone group. Interpretation: The primary endpoint was met at the interim analysis, showing a statistically significant and clinically meaningful improvement in progression-free survival with camrelizumab plus carboplatin and pemetrexed versus chemotherapy alone in all patients, supporting camrelizumab plus carboplatin and pemetrexed as a first-line treatment option for Chinese patients with advanced non-squamous NSCLC without EGFR and ALK alterations. The trial is being continued to collect long-term outcomes in all patients and carry out confirmatory statistical testing for progression-free survival in the PD-L1–positive population. Funding: Jiangsu Hengrui Medicine.